PTH-078 Increasing Adherence to BSG Guidelines for Cancer Surveillance in IBD - Effective Strategies. (17th August 2016) - Patel, RN; Mogwanja, O; El-Gazzar, Y
Abstract : Introduction: Colorectal cancer (CRC) is the fourth commonest cancer worldwide. Inflammatory bowel disease (IBD) is one of the many risk factors. Ulcerative colitis (UC) and Crohn's colitis both increase the risk of developing CRC by greater than 15 fold compared to the population without IBD. The National Institute for Health and Care Excellence (NICE) produced evidence-based recommendations in 2011 on the colonoscopic surveillance for prevention of CRC in people with UC, Crohn's disease or adenomas. These are broadly consistent with those in the BSG 2010 guidelines. One of the key recommendations is that chromoscopy (pan-colonic dye spray) is the technique of choice. Methods: We compared results from two audits (2012/13 and 2014/15) performed at Barking, Havering and Redbridge University Hospitals (BHRUH), each assessing adherence to the key features of the BSG guidelines. The interventions made between auditing included; adding a 'surveillance' option to the endoscopy request form, specifying 'dye spray' on the request and clerical staff dedicating 3 points (i.e more time) to perform the procedure. Results: 100 patients undergoing surveillance colonoscopy from September 2014 to August 2015 at BHRUH (49% male, 65% UC) were analysed compared with 35 patients in the period September 2012 to August 2013 (66% male, 97% UC). The number of chromoscopies performed for CRC surveillance in IBD patients increased from 1 in the initial audit to 30 in the follow up audit, after implementation of changes (p = 0.003). 23% of colonoscopies were performed in patients with less than 10 years duration of disease in the first audit compared with 9% in the second (p = 0.03). Polyps and dysplasia were identified in 20% and 8.6% of patients in 2013, respectively. This is compared to 31% (p = 0.21) and 8% (p = 0.91)in 2015. Conclusion: Adaptations to the way in which endoscopies are requested at BHRUH along with increased awareness amongst clerical staff booking the more time consuming surveillance colonoscopy has resulted in a significant increases in chromoscopy rates. However, there has not been a corresponding increase in the number of polyps or adenomas detected. This may be explained by the overall improvement in the quality of white light endoscopy and technical ability of endoscopists. Further work comparing chromoscopy, narrow band imaging and white light endoscopy in the detection of early cancers in IBD is required. References: 1 Colonoscopic surveillance for prevention of colorectal cancer in people with ulcerative colitis, Crohn's disease or adenomas. NICE Guidelines, 2011. 2 Guidelines for colorectal cancer for screening and surveillance in moderate and high risk groups (update from 2002). BSG Guidelines, 2010. Disclosure of Interest: None Declared